(untitled) (Bangladesh Journal of Medical Science, 2017)
Objective: The aim of our study was to evaluate whether insertion of a subcutaneous closed suction vacuum drain at incisional surgical site reduces the incidence of surgical site infection (SSI) in post operative cases of exploratory laparotomy for perforative peritonitis. Methods: An institutional based randomized control study was performed with two hundred patients each included in the study (with drain) and control (without drain) group. Both groups were statistically similar in terms of various variables and thus comparable. All continuous variables were reported as mean ± SD and compared across groups using unpaired t-test. All categorical variables were reports as n (%) compared across groups using Chi-square test for independence of attributes. Result: Use of a subcutaneous closed suction vacuum drain results in statistically significant reduction in wound infection (58% vs 16%; p < 0.001). The most common organism causing SSI was found to be Escherichia Coli accounting for 62.5% and 62.7% of cases in drain group and control group respectively, followed by Klebsiella (12.5% vs 24.14%). Conclusion: Use of a subcutaneous closed suction vacuum drain is effective in reducing SSI in contaminated surgery like that for perforative peritonitis and also leads to reduction in SSI related complications like wound disruption, patient discomfort, bad cosmesis, prolonged hospital stay, antibiotic use and increased cost. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.85-90